Beatriz Sarlo, La batalla de las ideas (1943-1973) - José Luis de Diego (Prismas, 2002)
Beatriz Sarlo, La batalla de las ideas (1943-1973), Biblioteca del Pensamiento Argentino, tomo VII, Buenos Aires, Ariel Historia, 2001, 468 páginas